cDNA ENCODING GROWTH HORMONE FROM HUMPBACK GROUPER (Cromileptes altivelis) - Mochamad Syaifudin; Alimuddin; Utut Widyastuti; Agus Oman Sudrajat; Komar Sumantadinata; Ratu Siti Aliah (BIOTROPIA, 2007)
Growth hormone (GH) that plays an important role in growth, reproduction, seawater adaptation, and immune function was isolated and sequenced from humpback grouper, Cromileptes altivelis. The cDNA was isolated from pituitary using RT-PCR. The 618 bp open reading frame encodes a 205 amino acid (aa) protein, which represents an 18 aa signal peptide followed by a 187 aa mature GH polypeptide. The fragment contained conserved domain of somatotropin–1, somatotropin–2, casein kinase II phosphorylation, protein kinase C phosphorylation, N–myristoylation and N–glycosilation. The similarity of deduced protein of humpback grouper GH was 65.0 - 89.5% with other fishes